(untitled) (Comillas Journal of International Relations, 2014)
Since the concept of public diplomacy was developed in the 1960’, its practitioners have accepted that sovereign states are not the only actors of international relations. On the contrary, there is a wide range of actors in the International Society, such as corporations, media, universities, think tanks. Even global public opinion could be considered an actor by itself. In the actual context where states are starting to loose their sovereignty and the public sector is becoming proportionally less important in Western economies, there is a growing tendency towards privatization of international relations. This tendency reflects on two concepts: polylateralism and new public diplomacy, which consists in direct relations among different countries public opinions, with no participation of sovereign states. We could be witnessing a completely new model: a private public diplomacy that would be based on a sovereign states definitive withdrawal from their monopoly on international relations in favour of the private sector.